Isochroman- and 1,3-dihydroisobenzofuran-annulation on carbohydrate templates via [2+2+2]-cyclotrimerization and synthesis of some tricyclic nucleosides - Suryawanshi, Sharad B.; Dushing, Mangesh P.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2010)
The synthesis of enantiopure tricyclic systems comprising isochroman or dihydroisobenzofuran units integrated with sugar templates has been documented. The alkyne cylotrimerization reaction has been employed with easily accessible sugar diynes for the key bicyclic ring construction and thus a provision to alter the functional groups on the newly formed aromatic rings. By selecting two representative trimerization products, we have synthesized the tricyclic nucleosides by simple synthetic manipulations. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Dihydroisobenzofuran; Dihydroisobenzopyran; Modified nucleosides; Vorbruggen reaction; [2+2+2] cyclotrimerization

Target cum flexibility: an alkyne [2+2+2]-cyclotrimerization strategy for synthesis of trinem library - Ramana, C. V.; Dushing, Mangesh P.; Mohapatra, Sradhanjali; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron Letters, 2011)
A rapid access to the central 4,5,6-tricyclic core of 4,5,6-trinems has been achieved by employing the alkyne [2+2+2]-cyclotrimerization as the key and final reaction in the synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Target cum flexibility: synthesis of C(3 `)-spiroannulated nucleosides - Dushing, Mangesh P.; Ramana, C. V. (Tetrahedron Letters, 2011)
We report a simple strategy for the synthesis of a collection of C(3')-spirodihydroisobenzo-furannulated nucleosides featuring a [2+2+2]-cyclotrimerization as the key reaction. The cyclotrimerization reactions are facile with the unprotected nucleosides having a diyne unit. When both alkynes of the diyne are terminal, the regioselectivity is poor. However, when one of the terminal alkynes is additionally substituted, the cyclotrimerizations are highly diastereoselective. Since the key bicycloannulation is the final step, this strategy provides flexibility in terms of the alkynes and is thus amenable for the synthesis of a focussed small molecule library. (C) 2011 Published by Elsevier Ltd.
Keywords: Dihydroisobenzofuran; Modified nucleosides; Tanaka catalyst; Willkinson catalyst; [2+2+2]-Cyclotrimerization